2022
DOI: 10.3389/fphy.2022.834571
|View full text |Cite
|
Sign up to set email alerts
|

Water in Deep Eutectic Solvents: New Insights From Inelastic Neutron Scattering Spectroscopy

Abstract: The effect of water on the physicochemical properties of deep eutectic solvents (DES) is a trending research topic. In this work, inelastic neutron scattering (INS) spectroscopy, was used to probe intermolecular interactions in the water-deep eutectic solvent mixtures for the cases of choline chloride (the hydrogen bond acceptor) and three different hydrogen bond donors, with different degrees of acidity: urea, glycerol and lactic acid. It was found that quenching samples in liquid nitrogen is a procedure that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 45 publications
(78 reference statements)
0
15
0
Order By: Relevance
“…For freshly prepared (from overnight vacuum-dried constituents) DES, the water content is measured to be 0.6% (w/w) and in IL, it is 0.7% (w/w). It was reported that highly hygroscopic choline chloride-based binary DES contains ∼0.2–0.8% water (w/w) depending on the second constituent (diol, triol or urea). For squalane, the water content is measured to be 0.3% (w/w).…”
Section: Methodsmentioning
confidence: 99%
“…For freshly prepared (from overnight vacuum-dried constituents) DES, the water content is measured to be 0.6% (w/w) and in IL, it is 0.7% (w/w). It was reported that highly hygroscopic choline chloride-based binary DES contains ∼0.2–0.8% water (w/w) depending on the second constituent (diol, triol or urea). For squalane, the water content is measured to be 0.3% (w/w).…”
Section: Methodsmentioning
confidence: 99%
“…As can be seen from Table S2, the electrostatic attraction energies in water-containing systems for interaction pairs Cl À -TIP3 (H1 atom) (MD simulations on systems containing DES + water displayed that water molecules tend to preferentially bond to the chloride anion and subsequently, the amount of choline cation and chloride anion interactions is reduced. [37] ) and OA of choline-TIP3 (H1 atom) at a temperature of 343 K are larger and stronger. This quantity has a downward trend with increasing temperature in the presence of LUA, so that, at the temperature of 343 K, we see electrostatic repulsion interactions for LUA (HA atom -Cl À and LUA (O2 atom)-TIP3 (H1 atom).…”
Section: Interactions Energiesmentioning
confidence: 95%
“…DESs maintain the identities of their components, which interact via hydrogen bonding, as opposed to covalent bonding. Further, DESs remain in a liquid state: molecular dynamics simulations and inelastic neutron scattering studies , revealed that the strength of hydrogen bonds between DES-forming components is weak enough to prevent them settling into a cocrystal . So far, depending on the chemical composition, five different categories of DESs are distinguished (Figure b).…”
Section: Deep Eutectic Solvents: From Chemistry To Bioinspired Synthesismentioning
confidence: 99%